KARAKTERISTIK SENYAWA ALKANOLAMIDA DARI MINYAK JARAK CASTOR DAN DIETANOLAMINE DENGAN KATALIS KOH - Fatma Sari Lubis (Universitas Muhammadiyah Jakarta, 2018)
Alkanolamide is an amide compound widely used in chemical, cosmetic and automotive industries. This compound has a